Advancement in narrow gap GMA weld joint of thick section of austenitic stainless steel to HSLA steel. (2017) - Anant, Ramkishor; Ghosh, P.K.
Abstract: In current welding research the development of new procedure to join thick section of dissimilar metal between austenitic stainless steel (γ-SS) and high strength low-alloy (HSLA) steel which are extensively used in elevated temperature applications like petrochemical plants and power stations is required to improve the quality of weld joint. In this paper the development and advanced study of narrowest possible gap GMA weld joint of thick (more than 25mm) γ-SS and HSLA steel and thermal behaviour of weld pool has been discussed for production of multipass single bead per layer narrow gap pulse current gas metal arc (P-GMA) weld joint of thick dissimilar plates free from any lack of fusion to the side wall. This advance procedure is simulated in ANSYS for production of a sound weld joint and the role of pulse current gas metal arc welding (P-GMAW) and its effect on shrinkage behaviour has been also discussed. The study of weld pool isotherm is very convenient to select the pulse parameter to produce the sound weld joint. The measurement of weld pool isotherm clearly indicate the proper selection of pulse parameter to produce sound fusion to the both side of groove wall specially in dissimilar weld joint.